PERILAKU MEMILIH ETNIS TIONGHOA Studi Kasus Perilaku Memilih Masyarakat Etnis Tionghoa Pada Pemilu Legislatif DPR Tahun 2009 Di Kabupaten Bangka - , Ranto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The presence of Tionghoa politician in Bangka Belitung has the contribution in various political arenas. Moreover, some candidates who competed from Tionghoa politician successfully with resplendent occupied the political position. Indeed, these phenomena present new colors in Bangka Belitungâs electoral, especially Tionghoa voters. Therefore, browsing how the pattern of political behavior among Tionghoa voters on legislative election, 2009 in Bangka Regency is interesting to observe. This study focused on the questions closely related with the primordial aspect, i.e. ethnicity, regional and religion which are attached to the Tionghoa voters. Through this study with mass (voters) approach itâs expecting could be explaining the pattern of political behavioral among Tionghoa voters. The study based on voters selected because it has believes that the most important factor that determines the successfulness of Tionghoa politician to occupy the political position is voters. This study using a sociological perspective which is observes that the Tionghoa voters will be considering the primordial aspect when they decided the political choice against certain politicians. The dataâs collecting done through a structured interview questionnaire sheet and documentation. This study were produced some important findings. First, ethnicity aspect has most important role which decisive associated with the dynamics of electoral among Tionghoa voters. More successful the politicians show Tionghoa identity then certainly the political support will flow from Tionghoa voters. Second, the representative of political logic works in Tionghoa community. Tionghoa voters will also considering regional representative aspect when they decided gave the political support. As long as the politicians can confirms as âLocal-Sonâ who representing the voters therefore the political support could be certainly for that politician. Third, the contribution of religion aspect cannot be ignored. The Tionghoa voters definitely will consider the religion background of politicians when they want to give the political support. More politician can shows they background as not Malaya, Tionghoa voters will give the political support. These third aspect was showed the interconnections and complementary. The identity factors with embed between the politician and voters become the instrument. Thus, the determination of primordial perspective becomes the benchmark and explanatory to observe the political behavior dynamics among Tionghoa voters in Bangka Regency.